A potential antifungal bioproduct for Microsporum canis: Bee venom - Armağan E. Ütük; Tülin Güven Gökmen; Hatice Yazgan; Funda Eşki; Nevin Turut; Şifa Karahan; İbrahim Kıvrak; Sedat Sevin; Osman Sezer (Onderstepoort Journal of Veterinary Research, 2024)
Natural treatment options for Microsporum canis dermatophytosis are being explored because of resistance to several antifungal medications. In this study, the potential antifungal effect of bee venom (BV), a natural antimicrobial agent, on M. canis was investigated. The antifungal effects of BV, fluconazole, itraconazole, amphotericin B and terbinafine were evaluated by the macrodilution method at various concentrations by modifying the microdilution method recommended by the European Committee on Antimicrobial Susceptibility Testing. All isolates were observed to be susceptible to terbinafine and fully resistant to fluconazole and amphotericin B. Minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) values of M. canis isolate 2 (Mc2) were determined as 8 µg/mL for itraconazole. The MIC and MFC values of BV were found to be 320 µg/mL for the Mc2 isolate and 640 µg/mL for the Mc6 isolate. The results showed that the isolates obtained from clinical samples in this study were highly resistant to all antifungal agents, except terbinafine. The increase in resistance indicates that antifungal drugs will become insufficient and ineffective over time and natural products such as BV should be evaluated as alternatives.